Cardioprotective potential of the antioxidant-rich bioactive fraction of Garcinia pedunculata Roxb. ex Buch.-Ham. against isoproterenol-induced myocardial infarction in Wistar rats - Bhattacharjee, Swarnali; Elancheran, R.; Dutta, Kasturi; Deb, Prashanta Kumar; Devi, Rajlakshmi (Frontiers in Pharmacology, 2022)
The study aimed to characterize the phenolic compounds in Garcinia pedunculata extract and assess each potential antioxidant activity as well as its cardioprotective potential in isoproterenol-induced cardiac hypertrophy in an experimental animal model. In vitro antioxidant properties were determined using DPPH, ABTS, FRAP, and PMD assays. In vitro lipid peroxidation experiment was also performed with heart tissues. Cardioprotective and cardiotoxicity effects were determined using cell line studies. The cardioprotective effect of GP was assessed in a rat model of isoproterenol (ISO) induced cardiac hypertrophy by subcutaneous administration. Heart weight/tail length ratio and cardiac hypertrophy indicators were reduced after oral administration of GP. Additionally, GP reduced oxidative stress and heart inflammation brought on by ISO. In H9c2 cells, the antihypertrophic and anti-inflammatory effects of the extract of GP were seen in the presence of ISO, which was further supported by the in vivo observations. This study makes a compelling case for the possibility that supplementing with dried GP fruit can prevent heart hypertrophy by reducing oxidative stress and inflammation.